IMAGE OF 2023 FISU WORLD STUDENT GAMES IN DIGITAL STUDENT SOCIOCULTURAL ENVIRONMENT - Rapoport, L.A.; Narkhov, D.Y.; Narkhova, E.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to survey and analyze attitudes to the upcoming 2023 World Student Games image in the host mid-Urals university student communities using a social networking activity analysis and questionnaire survey on a specialty-specific basis. Methods and structure of the study. We run for the purposes of the study a digital questionnaire survey (on CAVI platform, with the survey data mathematically processed by D.V. Shkurin using Vortex software tools) of a representative student sample (n=333); and a social networking activity analysis of the VKontakte accounts (n=368) of the students from 18 universities in the Sverdlovsk Oblast [3, p. 66], in December 2020 through January 2021. The survey and social networking activity analysis were designed to profile attitudes to the 2023 FISU World Student Games, its perceived role for the federal and regional progress, and the physical education and sports devotions in the sample. Results and Conclusion. The study found a significant proportion of the sample demonstrating positive attitudes to the 2023 World Student Games – apparently as a result of the event promotion/ imaging initiatives. Further advocacy is recommended along these lines, including empowerment of the activists and special encouragements for the still passive/ uncertain student groups. Target efforts to shape up a positive image of the event using modern social and communication technologies will help improve the 2023 World Student Games organizing, management and hosting services, with special benefits for the student social networking activity. Of special interest in this context may be the PR campaigns, communication technologies and promotions (including the social networking ones) geared to engage the still passive/ hesitant students, with the potential communication toolkits including the linguistic means to encourage healthy considerations/ reflections, motivations and rationale for contributions to the mega-event – and facilitate the transition from the “Me and event” to "My event” mindsets. Such campaigning and promotions should be reasonably customized to the socio-cultural environments and specialties in the host student communities.